Facile and cost-effective synthesis of isocyanate microcapsules via polyvinyl alcohol-mediated interfacial polymerization and their application in self-healing materials. (18th January 2017) - He, Zhenglong; Jiang, Shuai; Li, Qifeng; Wang, Junwei; Zhao, Yuhua; Kang, Maoqing
Abstract: Core-shell microcapsules with a composite shell and liquid core containing isophorone diisocyanate (IPDI) were synthesized via interfacial polymerization in an oil-in-water emulsion using polyvinyl alcohol (PVA) as an emulsifier. IPDI and polymethylene polyphenylene isocyanate (PAPI) were directly mixed to form an oil phase at room temperature, followed by conversion to the core and shell of the capsules due to the different reactivities of IPDI and PAPI with diethylene triamine (DETA). The composite shell was composed of a cross-linked PVA outer layer and a dense polyurea inner layer originating from PAPI and DETA. The formation process and morphology of the capsules were studied by optical microscopy and scanning electron microscopy. The changes in the shell compositions during the synthesis process were characterized by Fourier transform infrared spectra analysis. At 600 rpm and a PVA concentration of 5 wt%, the capsules had an average diameter of 96 ± 23 μm. The weight per cent of the liquid core in the capsules was approximately 80%, and the molar ratio of IPDI and PAPI in the core was approximately 9, which was confirmed by 1 H NMR. The core residue of the microcapsules was more than 50 wt% after three months in air or 10 days in water. To confirm the applicability of the prepared isocyanate microcapsules for self-healing, the capsules were incorporated into epoxy resin. The core-shell morphology of the capsules in the epoxy coating demonstrated the good practical applicability of the capsules. The microcapsules were effective for the self-healing of the epoxy coating as well as the protection of metallic substrates from corrosion.